2005
DOI: 10.1021/jm050155n
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis and Evaluation of [11C]-(+)-4-Propyl-3,4,4a,5,6,10b-hexahydro-2H-naphtho[1,2-b][1,4]oxazin-9-ol as a Potential Radiotracer for in Vivo Imaging of the Dopamine D2 High-Affinity State with Positron Emission Tomography

Abstract: In vivo imaging of dopamine D2 receptors with agonist (as opposed to the more commonly employed antagonist) radiotracers could provide important information on the high-affinity (functional) state of the D2 receptor in illnesses such as schizophrenia, movement disorders, and addictions. We report here the radiosynthesis and evaluation of the potent D2 agonist (+)-4-propyl-3,4,4a,5,6,10b-hexahydro-2H-naphtho[1,2-b][1,4]oxazin-9-ol, (+)-3, labeled with carbon-11, as a potential radiotracer for imaging the high-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
184
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 222 publications
(198 citation statements)
references
References 48 publications
10
184
2
1
Order By: Relevance
“…PET studies were performed on a GE 64 slice PET/CT Discovery VCT scanner (GE Medical Systems, Milwaukee, WI) with an approximate 5-to 6-mm resolution, using the D3R radiotracer [ 11 C]PHNO, synthesized as described in Wilson et al (2005). On the day of the PET study, monkeys (n = 8) were initially anesthetized with 10-15 mg/kg (i.m.)…”
Section: Experiments 1: Relationship Between D3r Availability and Quinmentioning
confidence: 99%
“…PET studies were performed on a GE 64 slice PET/CT Discovery VCT scanner (GE Medical Systems, Milwaukee, WI) with an approximate 5-to 6-mm resolution, using the D3R radiotracer [ 11 C]PHNO, synthesized as described in Wilson et al (2005). On the day of the PET study, monkeys (n = 8) were initially anesthetized with 10-15 mg/kg (i.m.)…”
Section: Experiments 1: Relationship Between D3r Availability and Quinmentioning
confidence: 99%
“…buspirone in dominant vs. subordinate monkeys may occur because exposure to chronic environmental stress vs. enrichment leads to differential regulation of D2-like receptor subtypes as discussed above. Further pharmacokinetic experiments and brain imaging studies with selective radiotracers (eg, [ 11 C]PHNO, Wilson et al, 2005;Payer et al, 2014) will help to illuminate the mechanisms underlying the observed differences in the behavioral effects of buspirone and other D2-like drugs in dominant and subordinate monkeys.…”
Section: Influence Of Route Of Administrationmentioning
confidence: 99%
“…Radiosynthesis of [ 11 C]-( þ )-PHNO was performed as previously described (Wilson et al, 2005). Each subject was administered B9-10 mCi of tracer (Table 1) and scanned for 90 min.…”
Section: Image and Data Analysesmentioning
confidence: 99%